Tension Band Wiring for Chronic Acromioclavicular Joint Dislocations Rockwood Type III/ISAKOS Type IIIB - Thaib, Subhan; Ramdani, Setiyo (Faculty of Medicine, Universitas Padjadjaran, 2025)
Acromioclavicular joint (ACJ) dislocations account for 10% of shoulder injuries, with Rockwood type III being the most common. Despite its prevalence, there is no consensus regarding a gold standard surgical treatment for chronic ACJ dislocations. tients often delay seeking medical attention during the chronic phase, during which soft tissue healing capacity significantly declines. A 30-year-old male presented with persistent shoulder pain and restricted elevation two months after a motorcycle accident. The patient initially sought alternative treatment, later developed chronic pain and an inability to elevate the shoulder. Physical and radiograph examinations revealed a Rockwood type III ACJ dislocation. After treatment with the tension band wiring (TBW) technique, functional outcomes were assessed using the Disabilities of The Arm, Shoulder and Hand (DASH) and Constant scores. The Constant score improved from 61 to 92 and while the DASH score decreased from 45 to 5 in 3 months and 2 weeks post-operation. International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine (ISAKOS) subdivided Rockwood Type III injuries into IIIA (stable) and IIIB (unstable), with type IIIB requiring surgical treatment. Several studies suggested that mechanical stabilization with biological augmentation is sufficient in neglected cases. However, this technique is expensive and required specialized skill and expertise in shoulder arthroscopy. To overcome this challenge, TBW has emerged as a cost-effective and straightforward surgical technique that enables faster rehabilitation and provides a stable, pain-free shoulder without postoperative complications. It may serve as a viable treatment option, particularly in resource-limited or rural settings.